Analisis Stabilitas Perbankan Syariah dan Perbankan Konvensional di Indonesia Tahun 2008-2020 - Akhmad Taufiq Satrio Wibowo (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2024)
Banking stability is a crucial problem in the current economy, especially after the Asian economic crisis in 1997 and the global crisis in 2008. This research aims to analyze the stability of Islamic banking by including macroeconomic variables in the form of the BI rate, inflation, exchange rate. tariffs and GDP as variables. its independence. Several previous studies applied NPF/NPL which measures credit risk ratios to test bank stability. Current research uses Z-Score to test bank stability. This research aims to find out whether there are differences in the financial performance of Islamic and conventional banks from 2008 to 2020. Testing and data analysis methods use Eviews. The results of this research show that banking stability, both conventional and sharia, is a vital aspect in maintaining the integrity of a country's financial system. Z-score as an indicator provides a comprehensive picture of a bank's stability by considering internal and external risks. In the context of this research, the finding that the BI Rate has a negative impact on the stability of conventional banks highlights the importance of monetary policy in managing interest rates to maintain the health of the banking sector. On the other hand, the negative impact of inflation on the stability of conventional and sharia banks emphasizes the need to control inflation to prevent disruption to banking performance.